The study of features of control of technological process for receiving the apple snacks - Malezhik, Ivan; Dubkovetskyy, Igor; Bandurenko, Galina; Levkivska (Muzika), Tetiana; Strelchenko, Ljudmila (My University, 2016)
Drying, moisture content, apple snacks, snacks, apples, energy supply, peroxidase, blanching, sugar syrup, convective, vitamin C. The article is devoted to the use of modern methods of the study of vegetable raw material for apple snacks production. To establish the optimal variety of apples there was used the analysis of technological parameters that depend on their chemical composition, especially on the quantity of dry substances, sugar-acid index and food fibers content. The study of inactivation degree of oxidative enzymes and possibility to prevent the protopectin hydrolysis process allowed establish the effectiveness of preliminary preparation of apples. research-industrial drying setting, constructed by the authors, gave a possibility to study the different drying processes at the expanse of combination of convective and thermoradiative ways of energy supply and to establish the optimal regime of apple snacks drying. Стаття присвячена дослідженню використання сучасних методів досліджень рослинної сировини для виробництва яблучних снеків. Для встановлення оптимального сорту яблук використовували аналіз технологічних показників, які залежать від їх хімічного складу, зокрема кількості сухих речовин, цукро-кислотного індексу та вмісту харчових волокон. Дослідження ступеню інактивації окислювальних ферментів й можливості перешкоджання процесу гідролізу протопектину дозволила встановити ефективність попередньої підготовки яблук. Сконструйована авторами дослідно-промислова сушильна установка, дала можливість провести дослідження різних процесів сушіння за рахунок комбінування конвективного та терморадіаційного способу енергопідведення та встановити оптимальний режим сушіння яблучних снеків.
Keywords: кафедра технології консервування; кафедра процесів і апаратів харчових виробництв; drying; moisture content; apple snacks; snacks; apples; energy supply; peroxidase; blanching; sugar syrup; convective; vitamin C; сушіння; вологовміст; снеки; яблучні снеки; пероксидаза; бланшування; цукровий сироп; вітамін С